Simulation analysis of fin swimming with bi-fins - Motomu NAKASHIMA (The Japan Society of Mechanical Engineers, 2019)
The objective of this study was to simulate the swimming motion with bi-fins and investigate the effect of ankle joint motion by simulation. A model of a swimmer was constructed by utilizing the swimming human simulation model SWUM. The bi-fin was modeled as a series of five rigid plates. One rigid plate was connected to another by virtual springs and dampers. In order to determine the spring constants of the springs and damping coefficients of the dampers, static and dynamic bending tests were conducted. In order to determine the fluid force coefficients for the fin, an experiment in which the fin was located vertically in a pool and was moved horizontally by an air cylinder was conducted. In order to acquire the motion of swimming with fins, two swimmers were asked to perform maximal front crawl swimming with/without fins in an indoor swimming pool. The swimming motion was filmed by three cameras underwater and one camera on land. Using all of the input data, simulations reproducing the experimental trials were carried out. By the simulation, the developed simulation method was validated since the simulated swimming speeds were consistent with the experimental values in errors less than 6% of accuracy. By analyses with the validated simulation method, it was found that the smaller ankle joint movements resulted in a faster swimming speed. It was also found that the fixed angle of ankle joints affected the body pitch angle and that there is an optimum fixed angle for a swimmer to maximize swimming speed.